Role of NLRP3 inflammasome in diabetes and COVID-19 role of NLRP3 inflammasome in the pathogenesis and treatment of COVID-19 and diabetes NLRP3 inflammasome in diabetes and COVID-19 intervention - Zhang, Jiayu; Ma, Xuejing; Liu, Fuwei; Zhang, Deju; Ling, Jitao; Zhu, Zicheng; Chen, Yixuan; Yang, Pingping; Yang, Yanlin; Liu, Xiao; Zhang, Jing; Liu, Jianping; et al. (Frontiers in Immunology, 2023)
2019 Coronavirus Disease (COVID-19) is a global pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). A "cytokine storm", i.e., elevated levels of pro-inflammatory cytokines in the bloodstream, has been observed in severe cases of COVID-19. Normally, activation of the nucleotide-binding oligomeric domain-like receptor containing pyrin domain 3 (NLRP3) inflammatory vesicles induces cytokine production as an inflammatory response to viral infection.Recent studies have found an increased severity of necrobiosis infection in diabetic patients, and data from several countries have shown higher morbidity and mortality of necrobiosis in people with chronic metabolic diseases such as diabetes. In addition, COVID-19 may also predispose infected individuals to hyperglycemia. Therefore, in this review, we explore the potential relationship between NLRP3 inflammatory vesicles in diabetes and COVID-19. In contrast, we review the cellular/molecular mechanisms by which SARS-CoV-2 infection activates NLRP3 inflammatory vesicles.Finally, we propose several promising targeted NLRP3 inflammatory vesicle inhibitors with the aim of providing a basis for NLRP3-targeted drugs in diabetes combined with noncoronary pneumonia in the clinical management of patients.